STRATEGI PUBLIC RELATIONS DALAM UPAYA MEMBANGUN CITRA PT. PRUDENTIAL LIFE ASSURANCE - RA. Putri Mustika Sari (Jurnal Pustaka Komunikasi, 2020)
Prudential Public Relations as an insurance service company requires good and precise planning. Therefore, Prudential must be able to provide enormous benefits to the community. The purpose of this study was to determine the PR strategy of Prudential Life Assurance in building images and the factors that contribute to building the image. The theory used in this research is The Seven C Communication Theory, the paradigm used in this research is the constructivism paradigm. This study uses qualitative methods as a research method that does not use statistical formulas or numbers. The results showed that Prudential Life Assurance's Public Relations chose a management strategy in building an image by finding and collecting data about customer needs. They also help meet targeted customer needs with win solution techniques, building trust with their customers in communicating what customers need. Public relations supporting factors in order to build a company image through the implementation of true selling, hotel visits, school visits to introduce students to insurance, and alms to help underprivileged people so that people sympathize and get to know the Prudential Company better. That is the main thing of public relations planning, namely Marketing Communication.